Financial management for local government - Spearman, Kay.; Earthscan; United Nations Human Settlements Programme; Local Government and Public Service Reform Initiative; Open Society Institute (London : Earthscan, 2007)
"This series is designed to cover all aspects of sound financial management for local governments in developed and developing countries and economies in transition. Concepts of good governance, transparency and accountability are woven into the text of every chapter, and the needs and potential obstacles to greater decentralization and democracy are highlighted. Each volume is self-contained with its own Trainer's Guide, exercises and web resources. Chapters are divided into basic and advanced concepts and the detailed relationship of each topic to the others covered in the series is explained"--Publisher's description.
v. 1. Creating a financial framework -- v. 2. Managing the operating budget -- v. 3. Managing the capital investment plan -- v. 4. Managing performance.
"Revised and updated version of the Local government financial management (LGFM) series"--P. [v].
Title from cover.
"Published by Earthscan for and on behalf of the United Nations Human Settlements Programme (UN-HABITAT)"--P. [ii].
"HS/839/06E"--P. [ii].
Includes bibliographical references.
Keywords: Local finance; Local finance -- Problems, exercises, etc